Comparative Study on Flexible Link Aerator Using Arduino Programming and Dissolved Oxygen Meter - Md Zain, Badrul Aisham; Anuar, Fatin Farhana; Al-Shaibani, Najib (International Journal of Integrated Engineering, 2018)
This paper presents the comparative study on flexible link aerator using Arduino programming and dissolved oxygen meter. To maintain the level saturation of dissolved oxygen it is importance to control the mechanism. For control the flexible link aerator for generating dissolved oxygen it will collaborate with Arduino system. Arduino will attach together to flexible link aerator and give the instruction to motor according to the level of saturation dissolved oxygen had been set on it. For set the level of saturation dissolved oxygen it will design the instruction suitable for the Arduino programming language. To reduce the steady state error it will work with PID controller to achieve the best performance on flexible link aerator. The experiment will be conducted in the model scale tank. On Arduino the programming will be set into the rate of dissolved oxygen between 18 O_2% and 20 O_2%. The mechanism of flexible link aerator is by using flexible link with circle holes. The Arduino controller program and the dissolved oxygen meter show is difference value because the result dissolved oxygen meter is considering the temperature. The result of dissolved oxygen level and the PID controller parameter are shown based on the current dissolved oxygen level during the experiment. The flexible link aerator can control the dissolved oxygen level by using Arduino and the motor of flexible link aerator is controlling by PID controller.